1988
DOI: 10.1073/pnas.85.18.6949
|View full text |Cite
|
Sign up to set email alerts
|

Liposome formulations with prolonged circulation time in blood and enhanced uptake by tumors.

Abstract: The rapid clearance of circulating liposomes from the bloodstream, coupled with their high uptake by liver and spleen, has thus far been an obstacle to any attempts at targeting to tumors. We have assessed the impact of liposome composition on their clearance from the circulation in normal and tumor-bearing mice and on their uptake by tumors and various normal tissues. By selective changes in lipid composition, while maintaining a mean particle diameter of '100 nm, we have achieved up to a 60-fold increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
488
2
10

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 998 publications
(518 citation statements)
references
References 36 publications
14
488
2
10
Order By: Relevance
“…Pegylated liposomes covalently bind to proteins as the carrier and several lines of evidence demonstrated that pegylated therapeutic compound are more stable in circulation and are not easily removed by reticuloendothelial system (RES) and this formulation increases the adherence of drug to the cancer cell. In the other words it will result in enhancement of cellular drug absorption [9,[26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Pegylated liposomes covalently bind to proteins as the carrier and several lines of evidence demonstrated that pegylated therapeutic compound are more stable in circulation and are not easily removed by reticuloendothelial system (RES) and this formulation increases the adherence of drug to the cancer cell. In the other words it will result in enhancement of cellular drug absorption [9,[26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Considerable research effort has gone into the optimisation of the composition of liposomes in order to achieve maximal tumour targeting (Gabizon and Papahadjopoulos, 1988;Gabizon et al, 1990;Klibanov et al 1990). However, the effect of tumour-related factors on this process has not been explored in detail.…”
Section: Discussionmentioning
confidence: 99%
“…In order to facilitate the rational integration of liposome technology into current or novel therapeutic strategies, detailed knowledge of the factors which govern liposome distribution to tumours will be required. There is a considerable amount of data in the literature examining the effect of liposomal composition on their pharmacokinetics and biodistribution (Gabizon and Papahadjopoulos, 1988;Gabizon et al, 1990;Klibanov et al, 1990). However, there is relatively little known about the influence of tumour-related factors on liposomal tumour targeting.…”
mentioning
confidence: 99%
“…It is now generally recognized that preferential delivery of anticancer drugs to tumor sites following intravenous injection can be achieved by encapsulation of these drugs in large unilamellar vesicles (LUVs) exhibiting a small size (Ͻ100 nm diameter) and extended circulation lifetimes (circulation half-life in mice Ͼ5 h). [7][8][9] The accumulation of these drug delivery systems at disease sites, which includes sites of infection and inflammation as well as tumors, has been attributed to enhanced permeability of the local vasculature in diseased tissue. 10 A gene delivery system containing an encapsulated plasmid for systemic applications should therefore be small (Ͻ100 nm diameter) and must exhibit extended circulation life-times to achieve enhanced delivery to disease sites.…”
Section: Introductionmentioning
confidence: 99%